Augmented utilisation of possession time: Analysis for track geometry maintenance. (May 2016) - Famurewa, Stephen M; Juntti, Ulla; Nissen, Arne; Kumar, Uday
The demand for increased capacity on existing railway networks is a challenge for many Europe-based infrastructure managers; addressing this challenge requires augmented utilisation of track possession time. It is considered that large-scale maintenance tasks such as geometry maintenance can be improved; thus, reducing the on-track maintenance time and allowing more traffic. In this study, an analysis of track geometry maintenance was performed with the objective of reducing the required possession time. The procedure and models for planning and optimizing track geometry maintenance are presented. A statistical model that uses a simulation approach was used to determine the condition of the track geometry, and a schedule optimization problem was formulated to support intervention decisions and optimize the track possession time. The results of the case study show that optimizing the maintenance shift length and cycle length are opportunities to reduce the extent of track possession required for the maintenance of the track geometry. In addition, continuous improvement of the tamping process through lean analysis promises about a 45% reduction in the required possession time for a tamping cycle.